Circular economy, sustainability and fashion industry: a bibliometric analysis - Andreatta, Tanice (2024)
The present study gravitates around the circular economy, sustainability and the fashion industry approach, with the scenario of concern for the environmental impacts resulting from the phenomenon of fast fashion. The aim of this study was to realize a bibliometrics analysis of the Circular Economy, sustainability, and the fashion industry. The research procedure used was bibliometrics, and the appropriate proportions were saved, it allowed us to map the state of the art concerning the international scientific production on Circular Economy and the fashion industry in the bibliographic data platform Scopus. The sample consisted of 81 papers published between 2016 and 2021, and, for analysis, the Bibliometrix was used. Through the results obtained, it was found that there is a trend of increase in publications on the subject in recent years. The studies investigated are similar to understanding the Circular Economy as a breakthrough for the fashion industry. The publications are conditioned to an optimistic scenario, with research and innovations that allow the overcoming of the fast fashion model and the adoption of sustainable and circular practices. It is therefore essential that the issue is increasingly discussed, not only in the business environment; but especially with the consumer market and society.